Disjunctive programming-tabu search for job shop scheduling problem / Syarifah Zyurina Nordin ... [et al.] - Nordin, Syarifah Zyurina; Wong, K.L.; Hang, See Pheng; Saipan@Saipol, Hafizah Farhah; Abu Husain, Nurulakmar (2021)
A scheduling helps to reduce the production time which indirectly reduce the costs as well. In job shop scheduling, it does not have a fixed sequence of operations and has a wide range of possible schedule that can be arranged. Our objective is to determine the job order on the parallel machine and minimizing the makespan of the processing time. A tabu search (TS) algorithm has been implemented to solve the job shop scheduling problem. Disjunctive programming (DP) with shortest total and longest total processing time has been used to find the initial solution for TS method. A comprehensive testing on the comparison of the results on different tabu list length with the benchmark values is conducted to investigate the performance of the proposed approach. From the results, DP produces a good result in job shop scheduling problem at least with a gap of 0.53% from the benchmark problem.